Empowerment through sex education? Rethinking paradoxical policies. Issue 6 (2nd November 2017) - Naezer, Marijke; Rommes, Els; Jansen, Willy
Abstract: Youth empowerment is the main goal of sex education according to Dutch Government and NGO policies. Academics from different disciplines have argued, however, that the ideal of empowerment through education is problematic, because of the unequal power relations implicated in educational practices. Building on one-and-a-half years of online and offline ethnographic fieldwork among Dutch youth, this article argues that Dutch sex educational policies inhibit rather than encourage young people's empowerment by allowing only a limited number of sexual knowledge building practices to thrive while making others nearly impossible. In order to facilitate young people's empowerment, policies should aim to create space for young people to develop their own themes and priorities, to offer a multitude of perspectives, to set the pace and to use different strategies for sexual knowledge building, including learning by doing and online learning. This requires a cultural shift that involves both an openness to young people's experimentation, and a change in existing power hierarchies based on age.